Factors Associated With Repeat Hiv Testing Among Mothers Attending Perinatal Clinics in Rural And Urban Set Ups of Kisumu County, Western Kenya - Orinda, Joseph (JOOUST, 2022)
Over one million children are living with HIV, contracted predominantly through infection from their mothers. The majority of these women and children are in the developing world with two thirds of the infected adults and over 90% of the world’s children with HIV in Africa. The purpose of this study was to ascertain the correlates of repeat HIV testing among mothers during perinatal period in Kisumu County. The study adopted a facility based cross-sectional study design and a convergent mixed method. Study populations were Women who attended Antenatal and Postnatal visitsin2018 in the respective health facilities. The target populations were women of reproductive age living in Kisumu County. Data was collected using structured questionnaires, mother and child clinic booklets and semi structured key informant interview guide for healthcare workers. Quantitative data was analyzed using both descriptive statistics and inferential statistics with the aid of STATA version 14 while qualitative data was analyzed using content analysis. A total of 407 mothers were sampled from the 4 health facilities. The mean age was 24.38 (SD 5.18). Out of 407 mothers enrolled in the study, the proportion of those who completed schedule of repeat HIV tests between first Antenatal Care visit through to postnatal visits were 82(20.15%) The data showed that overall repeat HIV testing rate during perinatal period is very low in Kisumu County. Individual factors which were found to influence repeat HIV testing were education, marital status, level of income, being accompanied by partner and knowledge of provider. Facility based factors which were found to influence repeat HIV testing were privacy of the rooms and waiting time. From IDIs, design of register and industrial action from Nurses were reported as hindrance to repeat HIV testing. There is need to do more awareness through the Kenya ministry of health and the partners in health sector.
Keywords: IV seroconversion; Rapid HIV test